Tracing the sources of parliamentary procedure in the French constitution of 3–4 September 17911. (4th May 2019) - Aschenbrenner, Peter J.
ABSTRACT: When the Assemblée Nationale Constituante (ANC) adopted the first French constitution, delegates composed 11 articles whose purpose was to guide and govern the behaviour of members in a future legislative assembly. Procedures in three of these articles required that a bill receive three readings during its progress through the assembly. Beginning with works of René Descartes (1637) and Galileo Galilei (1638), I located sources for procedures that guide and govern the work of law-makers, applying their reasoning to the process of legislation. I explain how investigators went about identifying variables that captured conditions of possible experience. Narrowing my focus to three articles in the 1791 constitution, I extracted variables pertinent to the three readings of a bill, along with the permissible range of values that the text of these articles assigned to each variable. An Excel 3D Surface chart presents procedural choices which were available to French delegates to the Assemblée Nationale Constituante, the body responsible for drafting the 1791 constitution. The Excel chart is based on arrays of variables and the values assigned from the text of these three articles; these are located in Section II Tenue des Séances et Forme de Délibérer / Conduct of Meetings and Form of Deliberation'.